The climate-triggered western shift of the confluence between the Dora Baltea and Po rivers (north-western Italy) during the late Holocene. (March 2019) - Giraudi, Carlo
The study on the migrations of the confluence between the rivers Po and Dora Baltea was based on a detailed observation of aerial photographs, field surveys and sediment stratigraphy. The age of the sediments and morphological features was based on radiocarbon datings, on the presence of archaeological settlements and ancient artefacts and on historical data. The aerial photographs of the GAI 1954 flight of the Italian Air Force were used because in the year 1954, some low terraces were still clearly visible, while today are almost completely obliterated because of the works for the improvement of the rice fields. A succession of nine fluvioglacial and fluvial terraces and many abandoned riverbeds have been identified: the interpretation of the morphological features made it possible to identify the Po and Dora Baltea evolution during the late Holocene. The study established that during the last 3000 years, the confluence of the Dora Baltea into the Po has constantly migrated to the west and that this migration occurred during alluvial phases dating back to the Iron Age, 2nd century BC–1st century AD, 5th century AD, 6th–8th century AD and 15th–19th century AD. The alluvial phases occurred during periods of increased floods in northern Italy and advances of the Alpine glaciers in northwestern Italy and Switzerland. Neither tectonic deformations nor anthropic actions seem to have influenced fluvial evolution in the last 3000 years. The westward migration of the confluence between the rivers was therefore triggered by climatic changes, but caused by the different responses of the catchments of the Dora Baltea and the Po rivers to climatic changes, and by the greater slope of the Dora Baltea flood plain.